Pendampingan Strategi Pemasaran Hasil Kreatifitas Pengolahan Media Ramah Lingkungan Panti Asuhan Kristen Tangmentoe - Astriwati Biringkanae; Mey Enggane Limbongan; Isak Pasulu; Grace Sriati Mengga; Lisa K. Wibisono (Jurnal Masyarakat Mengabdi Nusantara, 2024)
Community service is one of the three pillars of higher education, aiming to provide solutions to the problems faced by society, including in the aspect of economic empowerment. Panti Asuhan Kristen Tangmentoe is a non-governmental organization located in North Toraja, under the auspices of the Toraja Church. This orphanage has great potential in developing the creativity of its foster children, particularly in their skills in processing eco-friendly materials from bamboo waste. The challenge that arises is how to market the children's creative works. To ensure that these products can be enjoyed by a wider audience and generate positive economic impact, proper guidance is needed in marketing strategies. The stages implemented included product marketing training and mentoring, with evaluations conducted after each phase. This mentoring activity resulted in several positive impacts for Panti Asuhan Kristen Tangmentoe. The foster children and the orphanage staff were able to process bamboo materials into various creative products. These results not only pertained to improved skills and understanding of marketing strategies, but also included social and economic impacts on the orphanage. In terms of marketing, the training participants were able to implement the strategies taught. The products are now being marketed through social media and local e-commerce platforms, receiving positive responses from consumers.